DNA-directed nanofabrication of high-performance carbon nanotube field-effect transistors - Zhao, Mengyu; Chen, Yahong; Wang, Kexin; Zhang, Zhaoxuan; Streit, Jason K.; Fagan, Jeffrey A.; Tang, Jianshi; Zheng, Ming; Yang, Chaoyong; Zhu, Zhi; Sun, Wei (Science (American Association for the Advancement of Science), 2020)
Semiconducting carbon nanotubes (CNTs) are an attractive platform for field-effect transistors (FETs) because they potentially can outperform silicon as dimensions shrink. Challenges to achieving superior performance include creating highly aligned and dense arrays of nanotubes as well as removing coatings that increase contact resistance. Sun et al. aligned CNTs by wrapping them with single-stranded DNA handles and binding them into DNA origami bricks that formed an array of channels with precise intertube pitches as small as 10.4 nanometers. Zhao et al. then constructed single and multichannel FETs by attaching the arrays to a polymer-templated silicon wafer. After adding metal contacts across the CNTs to fix them to the substrate, they washed away all of the DNA and then deposited electrodes and gate dielectrics. The FETs showed high on-state performance and fast on-off switching. Science , this issue p. 874 , p. 878 High-performance field-effect transistors are constructed from carbon nanotube arrays positioned with DNA templates. Biofabricated semiconductor arrays exhibit smaller channel pitches than those created using existing lithographic methods. However, the metal ions within biolattices and the submicrometer dimensions of typical biotemplates result in both poor transport performance and a lack of large-area array uniformity. Using DNA-templated parallel carbon nanotube (CNT) arrays as model systems, we developed a rinsing-after-fixing approach to improve the key transport performance metrics by more than a factor of 10 compared with those of previous biotemplated field-effect transistors. We also used spatially confined placement of assembled CNT arrays within polymethyl methacrylate cavities to demonstrate centimeter-scale alignment. At the interface of high-performance electronics and biomolecular self-assembly, such approaches may enable the production of scalable biotemplated electronics that are sensitive to local biological environments.